The Role of Poetics at a Tense World Heritage Site: Pasargadae, Islamic Republic of Iran - Harris, Jennifer (Common Ground Publishing, 2012)
When Pasargadae, in the Islamic Republic of Iran, was designated a World Heritage site in 2004 it was praised for, among other values, its ancient connection to the Achaemenid Empire which is thought to be one of the first empires to respect cultural diversity in its multiple peoples. A contemporary western approach to interpretation would usually develop this aspect of the site making strong links to current social values. Social diversity, however, is not a value of the Iranian government. A chronological approach to interpretation of the site would necessarily result in interpreting its pre-Islamic past, also not necessarily desired by the government. A provocative, question-raising approach, likewise, would probably not gain official approval. This paper explores the possibility of poetics as the interpretive springboard at Pasargadae. It argues that poetics would open up the site to personal and shared experiences, while remaining within a preferred official interpretation. Poetics would allow the exploration of the historical, environmental and architectural values of the site. The openness of poetics should be adopted by western sites as an interpretive strategy, whether or not they face political challenges. The current western preference for developing sites within regional themes is producing repetition and denying site specificity.